X=-1
Y=1
Z=1
Step-by-step explanation
![\begin{gathered} 5x-3y+4z=-4\Rightarrow equation(1) \\ -4x+2y-3z=3\Rightarrow equation(2) \\ -x+5y+7z=13\Rightarrow equation(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r2xhrdx7gum7n1e2zt87dlz86gq3uxlka5.png)
Step 1
in order to eliminate y,
a))Mutiipy equation (3) by 5, then add the new equation to equation (1)
![\begin{gathered} -x+5y+7z=13\text{ }\Rightarrow eq(3)\text{ by 3} \\ 5x-3y+4z=-4\text{ }\Rightarrow eq(3)\text{ by 5} \\ \text{so} \\ -3x+15y+21z=39 \\ 25x-15y+20z=-20 \\ _(-------------------) \\ 22x+41z=19\Rightarrow equation(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nrjn0pdtd860colu7117qm5qdfbsita4vy.png)
so
now, equation(1) by 2, added to equaiton (2) by 3
![\begin{gathered} 5x-3y+4z=-4\Rightarrow equation(1)\cdot2 \\ -4x+2y-3z=3\Rightarrow equation(2)\cdot3 \\ so \\ 10x-6y+8z=-8 \\ -12x+6y-9z=9 \\ _(-----------------) \\ -2x-z=1\Rightarrow equation\text{ (5)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2qscyn2i3340d8t0fmsb5q4r8dzdnlovlv.png)
Step 2
now, use equation(4) and equation (5) to find x and z
![\begin{gathered} 22x+41z=19\Rightarrow equation(4) \\ -2x-z=1\Rightarrow equation\text{ (5)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p0so69zrh7zsh8z0zrasie4w8oe09s84zp.png)
a)in order to eliminate x, multiply equation (5) by 11, then add the result to equation(4)
![\begin{gathered} -2x-z=1\Rightarrow equation\text{ (5) by 11} \\ -22x-11z=11 \\ ad\text{d to equation(4)} \\ -22x-11z=11 \\ 22x+41z=19 \\ ------------ \\ 30z=30 \\ so \\ z=(30)/(30)=1 \\ z=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7suez2mfcimj3aylksslzxrttsscz8f56a.png)
hence
Z= 1
Step 3
now, replace the z value into equation(5) and isolate x
![\begin{gathered} -2x-z=1\Rightarrow equation\text{ (5)} \\ \text{replace} \\ -2x-(1)=1 \\ -2x-1=1 \\ add\text{ 1 in both sides} \\ -2x-1+1=1+1 \\ -2x=2 \\ \text{divide both sides by -2} \\ (-2x)/(-2)=(2)/(-2) \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sxksyokatczm7ij3oge9hicvokzpo3d4cn.png)
so
X=1
Step 4
finally, replace X and Z value into equation (1), then solve for x
![\begin{gathered} 5x-3y+4z=-4\Rightarrow equation(1) \\ 5(-1)-3y+4(1)=-4 \\ -5-3y+4=-4 \\ \text{add like terms} \\ -3y-1=-4 \\ \text{add 1 in both sides} \\ -3y-1+1=-4+1 \\ -3y=-3 \\ y=(-3)/(-3) \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o70715o5zxyfiji10vk5o8bv8y790lcasp.png)
therefore,
Y=1
so, the answer is
X=-1
Y=1
Z=1
I hope this helps you